The mechanism of action and performance of dialkyl 3,5-di-t-butyl 4-hydroxy benzyl phosphonates as a new antiwear additive - Choi, U.S.; Kwon, O.K.; Lansdown, A.R. (1991)
A study of the effect of a series of additives in lubricating oil was carried out using a four-ball wear test machine. The ethyl derivative, diethyl 3,5-di-t-butyl 4-hydroxy benzyl phosphonate (DEP), of a series of newly synthesized derivatives showed excellent antiwear performance compared with zinc dialkyl dithio phosphate and TCP under high temperature and speed conditions. An approach based on the thermally activated wear theory has been applied. To investigate the hydrogen-scavenging role of the DEP additive, a thermal degradation test was conducted and 1H nuclear magnetic resonance spectroscopy was used to identify the substitution reaction of hydrogen free radicals in the heated oil. On the basis of the experimental results, a new concept of antiwear mechanism was established and tested. The new additive showed the function of hydrogen and free-radical scavenging and was found to be a highly effective antiwear additive. ？ 1991.